Renal artery thrombosis. A case of acute flank pain in a patient with a new onset of renal failure and atrial fibrillation - Poggiali, Erika; Ferrari, Maria Giovanna; Botti, Camilla; Michieletti, Emanuele; Vercelli, Andrea (Acta Biomedica Atenei Parmensis, 2023)
Renal artery thrombosis is a severe and often misdiagnosed entity, that represents a true medical emergency in which renal infarction can occur. The diagnosis is often a challenge for the emergency physicians since it can mimic other more common diseases, including renal colic. We report the case of an 82-year-old man who presented to our emergency department for abdominal pain, nausea, and vomiting resulting from right renal artery thrombosis and infarction caused by misdiagnosed atrial fibrillation. Starting from our experience, we recommend to always keep renal thromboembolism in the differential diagnosis in a patient with sudden onset of flank/abdominal pain, high levels of lactate dehydrogenase and/or haematuria since early diagnosis and proper treatment are the keys to rapid recovery.